PENGARUH MODEL PEMBELAJARAN COOPERATIF TIPE INTEGRETED READING AND COMPOSATION (CIRC) TERHADAP HASIL BELAJAR MEMBACA PEMAHAMAN SISWA - jauhari, saprudin; ilhami, shofa (Universitas Hamzanwadi, 2015)
The aim of this study was to determine whether there is influence Kooperative Learning Model Type Integrated Reading and Composition (CIRC) on reading comprehension skills in grade IV SDN 1 Cape. This type of research is the study of this experiment using a pattern True Experimental Design with shapes Posttest-Only Control Design. This study was conducted SDN 1 Tanjung learning year 2014-2015. The hypothesis proposed in the form of the alternative hypothesis (Ha) is no influence of Cooperative Learning Model Integrated Reading and Composition (CIRC) on reading comprehension skills. In hypothesis testing used test